Apoptotic effect of lambertianic acid through AMPK/FOXM1 signaling in MDA‐MB231 breast cancer cells. (2nd May 2018) - Lee, Jae Hee; Lee, Hyo‐Jung; Sim, Deok Yong; Jung, Ji Hoon; Kim, Ka Ram; Kim, Sung‐Hoon
Abstract : Though lambertianic acid (LA) was known to exert antitumor effect in liver and prostate cancers, its underlying anticancer mechanism is never reported in breast cancers so far. Thus, in this study, apoptotic mechanism of LA was elucidated in MDA‐MB‐231 breast cancer cells. Here, LA increased cytotoxicity in MCF‐7 and MDA‐MB‐231 cells; enhanced sub‐G1 population, G2/M arrest, and cleaved poly(ADP‐ribose) polymerase; activated phosphorylation of AMP‐activated protein kinase (AMPK)/acetyl‐CoA carboxylase pathway; and also suppressed phosphorylation of AKT and the expression of forkhead box M1 (FOXM1), X‐linked inhibitor of apoptosis protein, B‐cell lymphoma 2, and CyclinB1 in MDA‐MB‐231 cells. Furthermore, AMPK inhibitor compound C reversed the effect of LA on FOXM1, Cyclin B1, and cleaved poly(ADP‐ribose) polymerase in MDA‐MB‐231 cells. Notably, immunoprecipitation revealed that LA disturbed the direct binding of AKT and FOXM1 in MDA‐MB‐231 cells. Overall, these findings suggest that LA‐induced apoptosis is mediated via activation of AMPK and inhibition of AKT/FOXM1 signaling pathway.